The shortfall of sociality: group-living affects hunting performance of individual social spiders. (20th July 2018) - Harwood, Gyan; Avilés, Leticia
Abstract : Ineffective solitary hunters likely fail to pass on their genes, but social hunters may benefit from others' spoils and be shielded from natural selection. We examine hunting performance in solitary and group-living cobweb spider species, finding that individuals from group-living species, especially those from large groups, were slower to react to prey and captured fewer prey. Group-living may thus negatively affect individual performance, potentially impeding social species' ability to evolve back to less social states. Abstract: Ineffective hunters in cooperative foraging groups may be shielded from natural selection by their more effective group mates, whereas those living solitarily would starve and thus be removed from the population. The problem may be exacerbated in large groups where it may be easier for individuals to withhold participation. Group foragers may thus be ineffective individual hunters or exhibit greater inter-individual variation in hunting abilities, in particular, when living in large groups. We test these hypotheses in spider species of the genus Anelosimus that differ in their level of sociality and, among social species, in colonies of different sizes. We found that individuals from the more social species, and those from larger groups, reacted more slowly to prey than those from solitary species or small groups. Individuals from these categories also had greater inter-individual variation in reaction times. Individuals from large social groups also had lower prey-capture success than those from small ones. These differences may have been driven by the size of the group from which the social individuals were taken, as those from small colonies behaved similarly to individuals of the 2 less social species. This finding suggests that hunting ability may develop as a phenotypically plastic trait.